Influences on student motivation and independent learning skills: cross-cultural differences between Hong Kong and the United Kingdom - Lo, Noble Po-kan; Bremner, Pauline A. M.; Forbes-McKay, Katrina E. (Frontiers in Education, 2024)
This study examines the ways in which different influences upon student motivation and the development of independent learning skills might be constituted across students learning within different educational cultures. Previous studies into student motivation and independent learning suggest the potential for differing conceptualisations of independent learning (IL) and its strategies (ISL), prompting questions as to the sources of these distinctions. One theory is that they might be influenced by differing cultural constructions of these concepts, or may be linked to different motivations with respect to the purposes and outcomes of education. This study addresses a research gap with respect to these differences across British and Chinese contexts, examining the responses of students across a university in Scotland and a university in Hong Kong. Through undertaking mixed-methods research consisting of quantitative analysis of questionnaires and thematic analysis of interview data, this research project compares the conceptualisations of IL and ILS across both these concepts and the role that student motivation might play within either context.